POLYCYCLIC AROMATIC HYDROCARBONS FORMATION IN DIFFERENT TYPES OF CHARCOAL GRILLED MEAT - Viegas, Olga (2013)
The goal of this work was the quantification of carcinogenic polycyclic aromatic hydrocarbons(PAHs) in charcoal grilled beef, pork and chicken using domestic grilling conditions and estimation of intake per 100g of cooked meat. All samples were grilled at 200 ºC. The visual aspect of the final products was well-done. PAHs extraction was performed using sonication followed by purification on SPE, and analyses by high performance liquid chromatography and fluorescence detection. Different quantitative profiles were observed in meat samples for the eight PAHs selected as indicators of carcinogenic PAHs in foods (PAH8). Benzo[a]pyrene(BaP) usually described as PAHs marker was 0.41, 2.71 and 3.14 ng/g, respectively, in beef, pork and chicken). Concerning PAH8 the mean levels were 3.20, 20.58 and 24.97 ng/g in the same samples. BaP and PAH8 were significantly correlated (p < 0.05) with fat content of raw meat. Positive correlation between BaP and PAH8 indicates that BaP is a good marker of the occurrence of PAHs. The consumption of charcoal grilled fatty meat leads to an extremely high dietary exposure to PAHs.